Mystery of Intron Gain - Fedorov, Alexei; Roy, Scott; Fedorova, Larisa; Gilbert, Walter (Genome Research, 2003)
For nearly 15 years, it has been widely believed that many introns were recently acquired by the genes of multicellular organisms. However, the mechanism of acquisition has yet to be described for a single animal intron. Here, we report a large-scale computational analysis of the human, Drosophila melanogaster, Caenorhabditis elegans, and Arabidopsis thaliana genomes. We divided 147,796 human intron sequences into batches of similar lengths and aligned them with each other. Different types of homologies between introns were found, but none showed evidence of simple intron transposition. Also, 106,902 plant, 39,624 Drosophila, and 6021 C. elegans introns were examined. No single case of homologous introns in nonhomologous genes was detected. Thus, we found no example of transposition of introns in the last 50 million years in humans, in 3 million years in Drosophila and C. elegans, or in 5 million years in Arabidopsis. Either new introns do not arise via transposition of other introns or intron transposition must have occurred so early in evolution that all traces of homology have been lost.